Rahasia Ketenangan Jiwa dalam Al-Qur'an - Sarihat cihat Nawawi (MAGHZA, 2021)
This article aims to examine the verses of Al-Quran that relate to actions that will give to faith and have implications for peace of soul. This type of research will be used is library research, which is collecting data from the library. Researchers used a thematic interpretation method regarding the tranquility of the soul. Sources of data to be taken consist of primary data sources, namely verses of the Al-Qur'an and secondary from books, commentaries, and other scientific journal articles. The result of the discussion is that there are many verses of the Al-Qur'an which mention the soul or the nafs. Verse of the Al-Quran that shows the soul is at peace is Surah Al-Fajr verses 27-30. Meanwhile, peace can be obtained through zikir as mentioned in Surah Ar-Ra'd verse 28. Apart from zikir, many acts of worship can be done to achieve peace of mind, such as praying, fasting, zakat, and reciting Al-Quran. Apart from being mentioned in the Al-Quran, these acts of worship are scientifically proven to be able to calm the soul.